Postural sway and perceived comfort in pointing tasks - Solnik, Stanislaw (2014)
In this study, we explored relations between indices of postural sway and perceived comfort during pointing postures performed by standing participants. The participants stood on a force plate, grasped a pointer with the dominant (right) hand, and pointed to targets located at four positions and at two distances from the body. We quantified postural sway over 60-s intervals at each pointing posture, and found no effects of target location or distance on postural sway indices. In contrast, comfort ratings correlated significantly with indices of one of the sway components, trembling. Our observations support the hypothesis that rambling and trembling sway components involve different neurophysiological mechanisms. They also suggest that subjective perception of comfort may be more important than the actual posture for postural sway.